PENERAPAN PRINSIP THE BEST INTEREST OF CHILD TERHADAP ANAK YANG MELAKUKAN TINDAK PIDANA KESUSILAAN (STUDI DI KEPOLISIAN DAERAH SUMATERA UTARA) - Sibarani, Fauzi Anshari; Ablisar, Madiasa; Marlina, Marlina; Ikhsan, Edy (BULETIN KONSTITUSI, 2022)
Law Number 11 of 2012 concerning the Criminal Justice System for Children (UU SPPA) brings fundamental changes to the juvenile justice system in Indonesia. This can be seen from the adoption of the principle of best interest for children which comes from Article 3 of the United Nations Convention on the Rights of the Child and ratified by the Indonesian government through Presidential Decree No. 36 of 1990 in the process of resolving cases of children in conflict with the law. This is in accordance with the concept of the State in Indonesia, namely the rule of law that applies proper legal principles and the application of the principle of The Best Interest of the Child to children in line with the concept of the rule of law of Indonesia. The principle of the best interest of the child or the principle of the best interest for children contained in the explanation of the Law on the Criminal Justice System for Children which states that the best interest for children is that all decision making must always consider the child's survival and development. The crime of decency that is contradicting the values and norms prevailing in Indonesia continues to occur today. Ironically, even the perpetrator of the crime of decency is a child. The implementation of the handling of children who are perpetrators of crimes of decency by the North Sumatra Regional Police cannot be equated with actions taken by adults. Diversion through the restorative justice approach must be put forward, as referred to in Article 1 number 6 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The North Sumatra Regional Police as the beginning of the gateway to the process of handling decency crimes committed by children in applying the principle of the best interest of the child does not always run smoothly, there are several obstacles to the police in applying these principles, one of which is that the Police does not have a written standard for application of the principle of the best interest of the child against the child offenders of decency crime. The principle of the best interests of the child has not fully become the main consideration, especially in handling in the police. The application of the principle of the best interests of the child must be proportional. The application of this principle is like the fruit of simalakama, on the one hand it aims to protect and nurture children who are in conflict with the law, but on the other hand there are interests of victims and society that must be protected from the point of view of justice.